2018
DOI: 10.1210/en.2018-00716
|View full text |Cite
|
Sign up to set email alerts
|

β-Cell Receptor Tyrosine Kinases in Controlling Insulin Secretion and Exocytotic Machinery: c-Kit and Insulin Receptor

Abstract: Insulin secretion from pancreatic β-cells is initiated through channel-mediated depolarization, cytoskeletal remodeling, and vesicle tethering at the cell membrane, all of which can be regulated through cell surface receptors. Receptor tyrosine kinases (RTKs) promote β-cell development and postnatal signaling to improve β-cell mass and function, yet their activation has also been shown to initiate exocytotic events in β-cells. This review examines the role of RTK signaling in insulin secretion, with a focus on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 98 publications
0
9
0
Order By: Relevance
“…The tyrosine phosphorylation at specific sites of the signaling molecule is precisely regulated by protein tyrosine kinases and protein tyrosine phosphatases (Tonks, 2006; Yu & Zhang, 2018). Although tyrosine kinases such as the insulin receptor, Src, and Fyn are acknowledged to play critical roles in hormone secretion (Jewell et al, 2011; Soares et al, 2013; Meijer et al, 2018; Oakie & Wang, 2018), only a very few PTPs that regulate the vesicle release machinery have been identified, and the structural basis of how these PTPs selectively dephosphorylate the key tyrosine phosphorylation sites governing exocytosis was unknown. In the current study, we demonstrated that PTP‐MEG2 is an important regulator of hormone secretion from the chromaffin cell, using a selective PTP‐MEG2 inhibitor in combination with cellular and electrochemical amperometric recording.…”
Section: Discussionmentioning
confidence: 99%
“…The tyrosine phosphorylation at specific sites of the signaling molecule is precisely regulated by protein tyrosine kinases and protein tyrosine phosphatases (Tonks, 2006; Yu & Zhang, 2018). Although tyrosine kinases such as the insulin receptor, Src, and Fyn are acknowledged to play critical roles in hormone secretion (Jewell et al, 2011; Soares et al, 2013; Meijer et al, 2018; Oakie & Wang, 2018), only a very few PTPs that regulate the vesicle release machinery have been identified, and the structural basis of how these PTPs selectively dephosphorylate the key tyrosine phosphorylation sites governing exocytosis was unknown. In the current study, we demonstrated that PTP‐MEG2 is an important regulator of hormone secretion from the chromaffin cell, using a selective PTP‐MEG2 inhibitor in combination with cellular and electrochemical amperometric recording.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we noticed an augmented expression profile of pathways that contribute to functionality and secretory properties of beta cells as well as other excitable cells. Several key receptors and downstream players representing G‐protein coupled receptor signalling, 43 Tyrosine–kinase receptor signalling 44 and calcium‐dependent signalling 45 as well as those proteins allowing vesicle docking and exocytosis 46–48 were upregulated in 3D‐beta. Consistent with this increase, 3D‐beta were able to respond to glucose by secreting C‐PEP indicating that they possess functional properties.…”
Section: Discussionmentioning
confidence: 99%
“…The tyrosine phosphorylation at specific sites of the signalling molecule is precisely regulated by protein tyrosine kinases and protein tyrosine phosphatases (Tonks, 2006;Yu and Zhang, 2018). Although tyrosine kinases such as the insulin receptor, Src and Fyn are acknowledged to play critical roles in hormone secretion (Jewell et al, 2011;Meijer et al, 2018;Oakie and Wang, 2018;Soares et al, 2013), only a very few PTPs that regulate the vesicle release machinery have been identified, and the structural basis of how these PTPs selectively dephosphorylate the key tyrosine phosphorylation sites governing exocytosis was unknown. In the current study, we demonstrated that PTP-MEG2 is an important regulator of hormone secretion from the chromaffin cell, using a selective PTP-MEG2 inhibitor in combination with cellular and electrochemical amperometric recording.…”
Section: Discussionmentioning
confidence: 99%